A Comparison of Chinese and Turkish Prepositions and the Strategies for Teaching Chinese Prepositions to Native Turkish Speakers - Lihua Li; Fatma Ecem Ceylan (Şarkiyat Mecmuası)
This study presents a comparative analysis focusing on the relationship between Chinese and Turkish prepositions and presents the strategies used for teaching Chinese prepositions to native Turkish speakers. The first part of this study examines differences between Chinese and Turkish prepositions. The second part of the study lists Chinese prepositions as classified according to Liu Yuehua’s (2001) classification of modern Chinese words alongside the Turkish equivalents, including affixes and postpositions. The third part of the study uses examples to illustrate Chinese prepositions and their Turkish equivalents. The final part of the study focuses on the teaching strategies used for Chinese prepositions. This study finds that, due to the complexity of Chinese prepositions and the characteristics of Turkish, no closed-class words occur in Turkish or the Turkish equivalents of Chinese prepositions. In addition, Chinese prepositions have much more complex structures in Turkish. When teaching Chinese prepositions, especially when teaching Turkish students with and elementary level of Chinese, teachers should not only help students learn the definitions of Chinese prepositions and their Turkish equivalents but also understand students’ native language. Teaching strategies used in this way will help achieve the goals.